PENGARUH BAHAN BONDING DAN INTERMEDIATE LAYER TERHADAP KEBOCORAN MIKRO RESTORASI KAVITAS KELAS II RESIN KOMPOSIT SILORANE - , Billy Sujatmiko ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Silorane a new composite resin matrix instead of in methacrylate resin matrix composites. Clinical applications of resin composite fillings often use an intermediate layer, intermediate layer helps prevent micro leakage at the edges of restoration and improve adaptation between the teeth and fillings. The purpose of this study is to determine influence the bonding materials and intermediate layer on micro leakage restoration class II resin composite silorane. In this study using 23 upper first premolars. The teeth is divided into groups A and B, divided by the base layer, group A with adhesive system silorane (SSA) and group B with bonding system VII methacrylate generation on the base layer. Group A is divided on to 3 groups: group A1 (with intermediate layer and SSA), A2 (with intermediate layer and without SSA), and A3 (without intermediate layer and without SSA). Group B is divided on to 3 groups: groups B1 (with intermediate layer and SSA), B2 (with intermediate and without SSA), and B3 (without intermediate layer and without SSA). All groups are performed with silorane composite resin filling. Data are analyzed using two way ANOVA tests and the followed by LSD tests The test results two way ANAVA tests show that there are significant differences in the influence of micro leakage of the bonding types in the cavity base and the presence of intermediate layer and bonding before silorane composite class II filling. In this study, concluded that there are influence micro leakages in the application bonding materials and intermediate with silorane composite class II filling.